An Assessment of the Relationship Between Office Rent and Vacancy Rate in Abuja, Nigeria - Udoekanem, N.B; Ighalo , J.I (Asian Journal of Empirical Research, 2016)
This study assessed the relationship between office rent and vacancy rate in Abuja, Nigeria. Data for the study was obtained from estate surveying and valuation firms which are active in the commercial property market in the city through field survey. The data utilised for the study comprised office rental values and office space data in the city for the period, 2001-2012. Results of data analysis revealed a statistically significant negative relationship between vacancy rate and office rent in the various commercial sub-markets in Abuja for the period, 2001-2012. This implies that office rent is inversely related to vacancy rate in the city. The study concludes that economic activities which are capable of creating office employment in the city should be encouraged as such activities could contribute to reducing office vacancy rate, thereby boosting office rental performance in the city.